Implementation Of Project-Based Learning Oriented To The Merdeka Learning Curriculum In The Form Of A Pancasila Student Profile With Global Diversity - Fitriyani Fitriyani; Titin Sunaryati; Vivi Muflida Karta Surya (Buana Pendidikan, 2023)
The concept of an independent learning curriculum that is applied in elementary schools is a solution to answer all education problems in Indonesia. Currently, the Independent Learning Curriculum that is applied includes strengthening the Pancasila Student Profile, which is a project-based co-curricular activity designed to strengthen the achievement of competencies, and character according to the student profile compiled based on Graduate Competency Standards. Research is carried out at SDS Bangun Mandiri by implementing implementation, namely by carrying out Market day activities which are entrepreneurial activities to train students to apply positive values as a manifestation of the independent learning curriculum as a form of implementation of the Pancasila student profile with global diversity. This research aims to teach and train students in elementary schools to learn entrepreneurship and love products that preserve local wisdom. This study used qualitative descriptive data research. Data collection techniques used in-depth interviews, observations, and documentation. The result obtained from this activity is that students can implement market day activities by selling products from various provinces in Indonesia and around the world.